Exploring survival rates in HIV-infected Ethiopian children receiving HAART: a retrospective cohort study - Yimam Getaneh; Yared Dejene; Birhanemeskel T. Adankie; Siti Qamariyah Khairunisa; Dominicus Husada; Kuntaman Kuntaman; Maria Inge Lusida (BMJ Paediatrics Open)
Background Studies have shown a high rate of mortality among adults despite the introduction of highly active antiretroviral therapy (HAART). However, long-term outcomes of HAART among children remain poorly documented in Ethiopia. This study aimed to estimate the survival rate and identify associated factors among HIV-infected children on antiretroviral therapy.Methods A retrospective cohort study was conducted from August to December 2022 in 13 health facilities (HFs) using records of 554 children (<15 years old) initiating HAART from 2007 to 2019. HFs were selected using probability proportional to the size of patients. Survival rate and predictors of mortality were estimated using Kaplan-Meier and Cox-proportional hazards, respectively. The analysis was done using STATA V.16.0.Result Overall mortality among HIV-positive children taking HAART in Ethiopia in 12-year follow-up was 25.5%. Moreover, the mortality rate was 24 per 100 child-year observation. Survival during the median 9.65 (95% CI=9.30 to 10.00) years of follow-up was 0.50. There was a significant drop in the survival rate from the 6th year of follow-up (0.96) to the 8th year (0.78) till the 12th year (0.18). By the end of the follow-up period, 172 (23.69%) were lost to follow-up. There was a high risk of mortality among female (adjusted HRs (AHRs) (95% CI) =1.35 (1.14 to 1.65)), those with poor adherence (AHR (95% CI) =1.29 (1.13 to 1.35)), CD4 count of ≤200 cells/mm3 (AHR (95% CI) =1.75 (1.33 to 2.30)) and baseline haemoglobin≤12 g/dL (AHR (95% CI) =1.8 (1.66 to 1.98)).Conclusion The significant drop in the survival rate as of the 6th year follow-up and the high loss rate to follow-up call for programme attention. Close follow-up of children with low CD4 count, low haemoglobin and poor adherence could help improve survival.